Investigação molecular do vírus da febre amarela em primatas não humanos do estado de Minas Gerais (2017, 2021-2022) e adaptação de teste de neutralização para o vírus da febre amarela - Gabriela Fernanda Garcia Oliveira (2023)
Infection with yellow fever virus (YFV; Orthoflavivirus flavi) can result in yellow fever disease (YFD). The virus is transmitted by a hematophagous arthropod vector during blood repast. Maintenance of YFV can occur in three cycles: sylvatic, with nonhuman primates (NHPs) as primary hosts and humans as incidental hosts; urban and intermediate/rural, with humans as primary hosts. In Brazil, where there is a great diversity of NHPs, the maintenance cycle of YFD is the sylvatic one, with vectors Haemagogus sp. and Sabethes sp.. Between 2017 and 2018, the country faced a major outbreak of YFD, with confirmed human and epizootic cases, especially in the southeast region and in Minas Gerais (MG). Since then, cases in humans and epizootics associated with YFV infection continue to be reported. The death of NHPs is investigated and their notification is mandatory due to their importance as sentinels of YFD. However, the use of carcass samples may limit some diagnostic methodologies. In this study, the objectives were to investigate YFV infection in samples of NHPs from MG by means of molecular biology techniques and to optimize a viral neutralization test using macerated liver tissue samples in place of serum. To this end, total RNA was extracted from samples of NHPs carcasses. Subsequently, the RNA was submitted to RT-qPCR protocol using primers and probe specific for the 5'UTR region of the YFV genome. To adapt viral neutralization assays, 50mg fragments of liver tissue from mice experimentally infected with YFV 17DD (n=6) and samples from a MOCK group (n=6) macerated in MEM medium (200μL) and clarified were used. Serial dilutions were then made and virus (YFV 17DD) was added for inoculation in triplicate (dilutions 1:20 to 1:160) in a monolayer of VERO cells in 12-well plates. YFV genome was detected by RT-qPCR in kidneys and brains (15/144 and 6/58, respectively) from 2017 NHPs carcasses whose livers were negative for YFV detection by RT-qPCR and in samples from NHPs collected in the years 2021 and 2022 (18/124). For the results of the adapted viral neutralization test, a significant difference was observed between the reductions of the MOCK and infected groups. The results generated here increase the number of NHPs infected by YFV in the year 2017 and corroborate the continued circulation of YFV in NHPs in the state of Minas Gerais in 2021 and 2022, they also demonstrate the feasibility of the proposed adaptation to the viral neutralization technique by plaque reduction using an alternative sample to serum.